2017
DOI: 10.1186/s12885-016-3002-x
|View full text |Cite
|
Sign up to set email alerts
|

The miR-34a-5p promotes the multi-chemoresistance of osteosarcoma via repression of the AGTR1 gene

Abstract: BackgroundChemoresistance hinders the curative cancer chemotherapy. MicroRNAs (miRNAs) are key players in diverse biological processes including the chemoresistance of cancers.MethodsA RNA-seq-based miR-omic analysis of osteosarcoma (OS) cells was performed to detect the levels of miR-34a-5p. Bioinformatics analysis revealed that AGTR1 is one of the target genes of miR-34a-5p. The mRNA and protein levels of AGTR1 were detected in both the miR-34a-5p-mimic transfected G-292 and miR-34a-5p-antagomiR transfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 40 publications
2
37
1
1
Order By: Relevance
“…Partially in line with this result, we found that miR-34a high expression was correlated with prolonged DFS and OS compared to low expression in this study, which partly resulted from its regulation of several pathways or genes, including c-MET and G1 phase regulators, to cause the inhibition of tumorigenesis and lymphatic invasion, thereby affecting recurrence of NSCLC patients (35). In addition, miR-34a increases the sensitivity of chemotherapy and radiotherapy, decreasing recurrence of NSCLC patients (36,37). Subsequently, Cox regression analysis was performed to evaluate factors affecting DFS and OS in this study, we also observed that plasma miR-34a was correlated with prolonged DFS and OS in univariate Cox model, while it could not independently predict DFS and OS of NSCLC patients in multivariate Cox model.…”
Section: Discussionsupporting
confidence: 82%
“…Partially in line with this result, we found that miR-34a high expression was correlated with prolonged DFS and OS compared to low expression in this study, which partly resulted from its regulation of several pathways or genes, including c-MET and G1 phase regulators, to cause the inhibition of tumorigenesis and lymphatic invasion, thereby affecting recurrence of NSCLC patients (35). In addition, miR-34a increases the sensitivity of chemotherapy and radiotherapy, decreasing recurrence of NSCLC patients (36,37). Subsequently, Cox regression analysis was performed to evaluate factors affecting DFS and OS in this study, we also observed that plasma miR-34a was correlated with prolonged DFS and OS in univariate Cox model, while it could not independently predict DFS and OS of NSCLC patients in multivariate Cox model.…”
Section: Discussionsupporting
confidence: 82%
“…Zhang et al showed that CAFs enhance the malignant phenotype transition of hepatocellular carcinoma through transferring miR-320a-devoid exosomes to cancer cells, and that the miR-320-PBX3 axis increases the motility of hepatocellular carcinoma cells via activating the MAPK pathway [ 43 ]. Although studies have shown the effect of dysregulated miR-34a-5p in colorectal cancer [ 25 ] and osteosarcoma [ 26 , 44 ], the underlying mechanisms of miR-34a-5p in OSCC progression have not been elucidated. Our study provides evidence that miR-34a-5p overexpression could inhibit the proliferation and motility of OSCC cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…miRNA regulates the important pathophysiological processes in the development, progression, metastasis and chemotherapy of osteosarcoma, providing new ideas for targeted therapy of osteosarcoma [12]. miR-34a-5p [13] and miR-20a-5p [14] can increase the chemosensitivity of osteosarcoma cells; miR-34a inhibits tumor invasion and metastasis of osteosarcoma by affecting C-IAP2 and Bcl-2 [15]. In addition, miR-34a can also reduce the self-renewal ability, tumorigenic activity and invasive ability of cancer stem cells [16].…”
Section: Discussionmentioning
confidence: 99%